The punitive grounds of dissolution of the commercial companies in Costa Rica - Anzora Solano, Johan Alberto (2026)
This article substantiates and explains the category of punitive dissolving grounds of business companies, based on recent legislative changes in criminal and tax matters. To this end, this article details the laws containing those sanctions and presents the main consequences arising from them. In conclusion, it calls the attention to the need to encourage doctrinal discussion on this subject, to lay the foundations for further academic research on the phenomenon of criminal liability of legal entities.